2023
DOI: 10.1002/cam4.6200
|View full text |Cite
|
Sign up to set email alerts
|

Patient and public involvement in cancer research: A scoping review

Sara Colomer‐Lahiguera,
Matthieu Steimer,
Ursula Ellis
et al.

Abstract: IntroductionPatient and public involvement (PPI) in research emphasizes the importance of doing research with, rather than for people with lived health/illness experience(s). The purpose of this scoping review is to investigate the breadth and depth of scientific literature on PPI in cancer research and to identify how is PPI applied and reported in cancer research.MethodsWe searched MEDLINE, Embase, CINAHL, and PsycInfo up to March 2022. All titles/abstracts and full‐text results were screened by two reviewer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 104 publications
0
3
0
Order By: Relevance
“…To strengthen our program, we look to add the involvement of program alumni to help with feedback and evaluation for our program. These planned changes are consistent with the increased attention to patient public involvement (PPI) in research design and recruitment (i.e., gatekeepers) in cancer programs, which we may find useful as our program continues to develop and is evaluated each year [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 68%
“…To strengthen our program, we look to add the involvement of program alumni to help with feedback and evaluation for our program. These planned changes are consistent with the increased attention to patient public involvement (PPI) in research design and recruitment (i.e., gatekeepers) in cancer programs, which we may find useful as our program continues to develop and is evaluated each year [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 68%
“…Currently, there is no published Swedish study evaluating the impact of public contribution in research, however some Swedish studies have explored experiences of public contribution in research [ 58 61 ]. Further, there is currently a lack of public contribution in research in the oncology field especially outside of Canada, the UK, and the USA [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…We hope our planned public contribution activities and the examination of the acceptability, feasibility, and perceived impact of these activities will contribute to the growing evidence of how to embed and evaluate public contribution in healthcare research. This is of particular importance given: (1) the current lack of public contribution in Swedish healthcare research and in the oncology field [ 62 ]; (2) the need to strengthen the evidence base concerning the impact of public contribution in research [ 19 , 62 , 66 ]; and (3) the need to enhance researcher understanding concerning how to best implement public contribution in research. We hope that adding public contribution to the CHANGE trial will provide other researchers with guidance on how to embed public contribution in clinical research and add to the growing evidence base concerning the impact of public contribution in research.…”
Section: Discussionmentioning
confidence: 99%
“…Although unintended, these requirements contribute to an already existing underrepresentation in research of patients and the public who are in a more vulnerable position. This may include people with learning difficulties, the elderly, or people from minority ethnic groups [ 26 ]. Additionally, online meetings tend to have a more formal nature, making it harder to feel connected to each other and to the project [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, systematic and standardised reporting of PPI approaches remains limited. To enhance future research using a PPI approach, it should be reported, precisely and self-consciously, how and at which level PPI was employed [ 26 ]. This will be guided in the EUonQoL project by using a tool called the Guidance for Reporting Involvement of Patients and the Public (GRIPP2) reporting checklist.…”
Section: Methodsmentioning
confidence: 99%